2017
DOI: 10.19082/5172
|View full text |Cite
|
Sign up to set email alerts
|

Bio-psycho-social factors affecting sexual self-concept: A systematic review

Abstract: BackgroundNowadays, it is believed that mental and emotional aspects of sexual well-being are the important aspects of sexual health. Sexual self-concept is a major component of sexual health and the core of sexuality. It is defined as the cognitive perspective concerning the sexual aspects of ‘self’ and refers to the individual’s self-perception as a sexual creature.ObjectiveThe aim of this study was to assess the different factors affecting sexual self-concept.MethodsEnglish electronic databases including Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 34 publications
0
37
0
1
Order By: Relevance
“…A systematic review on vaginismus found that partners of women with vaginismus can be characterized as inactive and indecisive men who often suffer from sexual dysfunctions [ 2 ]. Many women with vaginismus have also shown low self-esteem, frustration, guilt [ 17 , 18 ] and negative images of their body [ 18 , 19 ]. Some women even have gone through divorce and have shown suicidal tendencies [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review on vaginismus found that partners of women with vaginismus can be characterized as inactive and indecisive men who often suffer from sexual dysfunctions [ 2 ]. Many women with vaginismus have also shown low self-esteem, frustration, guilt [ 17 , 18 ] and negative images of their body [ 18 , 19 ]. Some women even have gone through divorce and have shown suicidal tendencies [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sexual dysfunction can also affect treatment compliance, and the ability to maintain relationships with partners and spouses, and can be associated with depression and suicide [8,9]. Normal sexual behavior and sexual function are considered to be markers of health and are components of personal and social quality of life, which have been difficult to achieve with current treatment regimes in patients with schizophrenia [10]. However, improved sexual function in patients with schizophrenia has been recognized to have a close relationship with improvements in personal and social quality of life [11].…”
Section: Introductionmentioning
confidence: 99%
“…The sexual–emotional health domain involves the management of the health and balance of the dynamic flow of change regarding inner emotional experiences as well as sexual and gender identity and expression. Cultivating connection with one’s authentic sexual self includes developing positive sexual self-esteem (Potki, Ziaei, Faramarzi, Moosazadeh, & Shahhosseini, 2017) as well as the continuing formulation of one’s arousal template, or personal erotic meaning associated with physiological responses of sexual arousal. For healthy intrapersonal integration, self-awareness, understanding, and acceptance constitute important ongoing processes.…”
Section: A Mindful Model Of Sexual Healthmentioning
confidence: 99%